Studying signals in particle detectors with resistive elements such as the 2D resistive strip bulk MicroMegas - Janssens, D.; Brunbauer, F.; Flöthner, K. J.; Lisowska, M.; Muller, H.; Oliveri, E.; Orlandini, G.; Riegler, W.; Ropelewski, L.; Schindler, H.; Scharenberg, L.; Utrobicic, A.; et al. (Journal of Instrumentation, 2023)
As demonstrated by the ATLAS New Small Wheel community with their MicroMegas (MM) design, resistive electrodes are now used in different detector types within the Micro Pattern Gaseous Detector family to improve their robustness. The extended form of the Ramo-Shockley theorem for conductive media has been applied to a 1 Mω/□ 2D resistive strip bulk MM to calculate the signal spreading over neighbouring channels using an 80 GeV/c muon track. For this geometry, the dynamic weighting potential was obtained numerically using a finite element solver by applying a junction condition and coordinate scaling technique to accurately represent the boundary conditions of a 10 × 10 cm2 active area. Using test beam measurements, the results of this model will be used to benchmark this microscopic modelling methodology for signal induction in resistive particle detectors.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Detector modelling and simulations II (electric fields; charge transport; multiplication and induction; pulse formation; electron emission; etc); Micropattern gaseous detectors (MSGC; GEM; THGEM; RETHGEM; MHSP; MICROPIC; MICROMEGAS; InGrid; etc); Particle tracking detectors